Investigation Of Recycled Plastic Piles For Support Of Structures In Expansive Shale Environments - Eric Brandner (Deep Foundations Institute, 2009)
Expansive soil formations can be found throughout the United States. When subjected to wetting, many of these formations have the potential to swell and exert large uplift forces which can significantly damage lightly-loaded structures. Designing an economical foundation that can resist uplift forces is critical to prevent damage to these structures. The current solutions to control uplift due to swelling soils, such as over-excavation and replacement of the expansive material, or drilled shafts, can be costly and problematic. Piles made from recycled polymer materials may provide a solution. Due to a lower coefficient of friction along the interface than piles made from traditional materials, solid recycled plastic piles can allow expansive soils to move nearly independently from the pile when wetted. This results in a much smaller magnitude of uplift force being transferred to the structure which minimizes the risk of significant structural damage. This paper presents the preliminary results of research conducted on the use of recycled plastic piles in an expansive shale environment. The preliminary phase of the project involved the installation of six 13 in. (330 mm) diameter recycled plastic piles at a test site on the South Dakota School of Mines and Technology campus. The piles varied in length from 15 ft. to 25 ft. (4.6m to 7.6 m). Two of the piles were subjected to a full-scale compression load test in order to determine ultimate capacity, while the additional four piles are being subjected to long-term monitoring of uplift movement. A cast-in-place concrete pile, with a diameter of 6 in. (152 mm) and length of 15 ft. (4.6 m), was also installed at the test site for monitoring. The preliminary results indicate that the use of solid recycled plastic piles is a viable alternative for support of lightly-loaded structures in expansive soil environments.